Development of an Online Resource for People Bereaved by Suicide: A Mixed-Method User-Centered Study Protocol - Leaune, Edouard; Lestienne, Laurène; Grandgenèvre, Pierre; Morgiève, Margot; Vaiva, Guillaume; Vieux, Maxime; Chalancon, Benoît; Laplace, Nathalie; Haesebaert, Julie; Poulet, Emmanuel (Frontiers in Psychiatry, 2021)
Introduction: Suicide bereavement is known to be highly distressing and is frequently associated with mental health problems. Despite high-level of need regarding mental and physical health, people bereaved by suicide display low level of help-seeking and perceived support in the aftermath of the loss. The lack of accessibility and reliability of face-to-face counseling resources is notably reported by suicide survivors. Online resources can enhance early access to help and support for people bereaved by suicide. The primary objective of the study is to design and implement an innovative and adaptive online resource for people bereaved by suicide according to their needs and expectation regarding online solutions dedicated to suicide bereavement. Methods: The ESPOIR2S study is a mixed-method user-centered study. ESPOIR2S seeks to build the resource from the perspectives and needs of both people bereaved by suicide and professionals or volunteers working in the field of postvention. The Information System Research (ISR) Framework is used to guide the design of the study through a 3-step research cycle. The structure of the ESPOIR2S study relies on a simultaneous collection of qualitative and quantitative data which will be collected and analyzed during a) the Relevance cycle through an online questionnaire and focus groups; b) the Design cycle through focus groups; and c) and the Rigor cycle through an online questionnaire and semi-structured interviews. The user-centeredness will be ensured by the active participation of people bereaved by suicide, members of associations for bereaved people and professionals of postvention. Discussion: The mixed-method and user-centered design of the ESPOIR2S study will offer an in-depth collection of the needs and expectation of suicide survivors regarding online resources. Through the implementation of an adaptive online solution, we aim to enhance the access to help and support for suicide survivors which are highly correlated with well-being and recovery.